Critical Thinking Of Students In Solving Ill-Structured Mathematical Problems: A Scoping Review - Sheren Nursyafiqoh Undaresta; Ros Maliah Ahmad; Aida Nur Aini; Yudhi Hanggara; Hermansah; Suryo Hartanto; Shalehoddin (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2026)
This study highlights the importance of developing critical thinking skills in modern mathematics, particularly when students face ill-structured problems. Using a scoping review method, the research followed five stages: formulating research questions, identifying relevant articles, removing duplicates, mapping data, and summarizing findings. Data were collected from Google Scholar, Publish or Perish, and Connected Papers, covering publications from 2015 to 2025. Based on the PRISMA selection process, 20 relevant articles were analyzed. The findings reveal that students’ critical thinking and mathematical problem-solving abilities in ill-structured contexts are still relatively low. Many students struggle with key aspects of critical thinking, such as verifying information, conducting in-depth analysis, and reflecting on their solutions. These limitations indicate that students are not yet fully equipped to handle complex, open-ended mathematical problems. Thematic analysis shows a shift in research focus over time. Between 2015 and 2020, studies primarily identified students’ difficulties and barriers. However, from 2021 to 2025, research has increasingly emphasized the development of higher-order thinking skills (HOTS), numeracy literacy, and preparedness for the Industrial Revolution 4.0. The study recommends future research to explore innovative learning interventions that integrate creativity, critical thinking, and ill-structured problem-solving.